Now's Muslim Customers Geliat on The Purchase of Halal Products (Case Study on Supermarket Tip Top in Jabodetabek) - Arsj, Febri Rakhmawati (AFEBI Economic and Finance Review, 2021)
Today's Muslims are Muslims who are very digital literate, have global insight and broad language skills, as well as have a deeply rooted Islamic identity with a sense of pride in Islamic traditions with local characteristics. In consuming halal products, the Muslim lifestyle nowadays pays close attention to the halal logo that is in every intake of food and drink that enters the body so that they have no doubt in consuming it. Tip Top Supermarket is a retail with an Islamic concept that offers all food and beverages with a halal logo. Indicators of lifestyle, namely activity, are the biggest factor for Muslims today in shopping for halal products. The research method used is descriptive quantitative by conducting surveys and distributing questionnaires to Tip Top Supermarket customers.Keywords : Muslim Zaman Now, Lifestyle, Halal